Diferentes dosis de capsaicina 0,075% más lidocaína 2% como anestésico local en castración de lechones - Santana Williams, Luis Roberto (2023)
Different doses of capsaicin were evaluated as local anesthetics in the castration of piglets. A DBCA was used with three repetitions for each treatment where: block 1 (5-day-old piglets); T1 (Capsaicin 0.5 g), T2 (Capsaicin 0.9 g) and control (no stimulus applied). For block 2 the same distribution was applied. It was possible to show that cortisol levels increased after castration: in T1 the cortisol levels of the 5-day-old piglets increased more than that of the 21-day-old piglets. While in T2 they decreased for piglets 5 days old, unlike those 21 days old, which increased. The dosage of capsaicin was identified to decrease cortisol levels in 5- and 21-day-old piglets. T2 presented lower levels of cortisol (17.62 ng/ml) in 5-day-old piglets, while in 21-day-old piglets T2 obtained the lowest levels (40.36 ng/ml). That is, the higher the dosage of capsaicin, the lower the cortisol levels. Finally, in the piglets after castration, a significant difference occurred due to the effect of capsaicin on GDP. Therefore, a statistically significant difference is denoted between T1 (5-day piglets 0.1782 kg/day and 21 days 0.4097 kg/day) and T2 (5-day piglets 0.1723 kg/day and 21 days 0. 4145 kg/day) compared to the control group (5-day-old piglets 0.1516 kg/day and 21-day-old piglets 0.3983kg/day).